Protein-dependent regulation of feeding and metabolism. (May 2015) - Morrison, Christopher D.; Laeger, Thomas
Highlights Dietary protein is an essential nutrient that is required for health. Variations in protein quality or quantity robustly alter food intake. The intake of protein appears to be regulated independently of other nutrients. Protein-specific mechanisms offer novel opportunities for the treatment of obesity.